Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Lnc-HIBADH-4 Regulates Autophagy-Lysosome Pathway in Amyotrophic Lateral Sclerosis by Targeting Cathepsin D - Jingxuan Huang; Yujiao Yu; Dejiang Pang; Chunyu Li; Qianqian Wei; Yangfan Cheng; Yiyuan Cui; Ruwei Ou; Huifang Shang (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is the most prevalent and lethal class of severe motor neuron diseases (MND) with no efficacious treatment. The pathogenic mechanisms underlying ALS remain unclear. Nearly 90% of patients exhibit sporadic onset (sALS). Therefore, elucidating the pathophysiology of ALS is imperative. Long non-coding RNA (lncRNA) is a large class of non-coding RNAs that regulate transcription, translation, and post-translational processes. LncRNAs contribute to the pathogenesis of diverse neurodegenerative disorders and hold promise as targets for interference in the realm of neurodegeneration. However, the mechanisms of which lncRNAs are involved in ALS have not been thoroughly investigated. We identified and validated a downregulated lncRNA, lnc-HIBADH-4, in ALS which correlated with disease severity and overall survival. Lnc-HIBADH-4 acted as a “molecular sponge” regulating lysosomal function through the lnc-HIBADH-4/miR-326/CTSD pathway, thereby impacting autophagy-lysosome dynamics and the levels of cell proliferation and apoptosis. Therefore, this study discovered and revealed the role of lnc-HIBADH-4 in the pathogenesis of ALS. With further research, lnc-HIBADH-4 is expected to provide a new biomarker in the diagnosis and treatment of ALS.

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

The expression discrepancy and characteristics of long non-coding RNAs in peripheral blood leukocytes from amyotrophic lateral sclerosis patients - Yujiao Yu; Dejiang Pang; Chunyu Li; Xiaojing Gu; Yongping Chen; Ruwei Ou; Qianqian Wei; Huifang Shang (Molecular Neurobiology, 2022)

Unique characteristics of the genetics epidemiology of amyotrophic lateral sclerosis in China - Qianqian Wei; Xueping Chen; Yongping Chen; Ruwei Ou; Bei Cao; Yanbing Hou; Lingyu Zhang; Hui-Fang Shang (Science China Life Sciences, 2019)

TMEM230 Mutations Are Rare in Han Chinese Patients with Autosomal Dominant Parkinson’s Disease - Qianqian Wei; Ruwei Ou; Qingqing Zhou; Yongping Chen; Bei Cao; Xiaojing Gu; Bi Zhao; Ying Wu; Wei Song; Hui-Fang Shang (Molecular Neurobiology, 2018)

Determining the Effect of the HNMT, STK39, and NMD3 Polymorphisms on the Incidence of Parkinson’s Disease, Amyotrophic Lateral Sclerosis, and Multiple System Atrophy in Chinese Populations - Yongping Chen; Bei Cao; Ruwei Ou; Qianqian Wei; Xueping Chen; Bi Zhao; Ying Wu; Wei Song; Hui-Fang Shang (Journal of Molecular Neuroscience, 2018)

Mutation Screening of the CHCHD10 Gene in Chinese Patients with Amyotrophic Lateral Sclerosis - QingQing Zhou; YongPing Chen; QianQian Wei; Bei Cao; Ying Wu; Bi Zhao; RuWei Ou; Jing Yang; XuePing Chen; Shinji Hadano; Hui-Fang Shang (Molecular Neurobiology, 2017)

Serum uric acid level is associated with the prevalence but not with survival of amyotrophic lateral sclerosis in a Chinese population - Zhenzhen Zheng; Xiaoyan Guo; Qianqian Wei; Wei Song; Bei Cao; Rui Huang; Ruwei Ou; Xueping Chen; Huifang Shang (Metabolic Brain Disease, 2014)